Beyond One-Size-Fits-All Approach: Teaching Multicultural Classrooms in South African Schools - Pfuurai Chimbunde; Boitumelo Benjamin Moreeng (IAFOR Journal of Education)
Teaching diverse student populations with varying cultural, linguistic, and experiential backgrounds is fraught with opportunities and challenges. In this paper, we examined the prospects and complexities in teaching multicultural classes and how teachers’ competencies could be improved. This conceptual paper uses the case of South Africa to respond to two questions: What are the opportunities and challenges in teaching multicultural classes and how can teachers’ proficiencies be enhanced? Using document analysis, the study deploys Gay’s (2000) cultural responsiveness theory which argues that teachers must understand and value the diverse cultural backgrounds of learners and adapt teaching practices to meet their needs. Understanding the possibilities and complexities that teachers face in their teaching could unlock new avenues in teacher-education programmes. Findings replicate that while teaching multicultural classes is crucial for nationwide integration, teachers lack the necessary training and preparation to teach multicultural classes, hence have limited pedagogical approaches and face communication and classroom management challenges. Considering these findings, the paper suggests a re-look to redefine teacher training and recommends employing professional learning communities to augment existing teacher competencies. The study contributes to discourses on how teachers’ practices can be recalibrated to suit the educational needs of diverse learners.